Hansenia weberbaueriana (Fedde ex H.Wolff) Pimenov & Kljuykov Extract Suppresses Proliferation of HepG2 Cells via the PTEN-PI3K-AKT Pathway Uncovered by Integrating Network Pharmacology and Iin Vitro Experiments - Feng, Yueqin; Hao, Fengjin (Frontiers in Pharmacology, 2021)
Previous studies have shown that Notopterygium incisum Ting extracts (NIE) has antitumor activity, but its mechanism in vitro is still unclear. In this study, we first combined network pharmacology with experimental evaluation, and applied a comprehensive strategy to explore and prove the therapeutic potential and potential mechanism of Notopterygium incisum. The mRNA expression profiles of PTEN, PIK3A and AKT1 are from the Cancer Cell Line Encyclopedia (CCLE) of the Broad Institute. Our results showed that NIE has a good inhibition on HepG2 cells, and a slight inhibition on other cells. The results of the CCLE database showed that PTEN/PIK3A/AKT1 mRNA expression were up-regulated in HepG2 cell. Through further study, it was found that NIE increased the release of LDH, induced early and late apoptosis and increased ROS level in HepG2 cells. Western blot showed that NIE regulates the expression of mitochondrial apoptosis-related proteins. Meanwhile, the expression of PTEN was increased and the expression of phosphorylated PI3K and Akt was down regulated after NIE treatment. Our results show that NIE promotes HepG2 cells apoptosis via PTEN-PI3K-Akt signaling pathway. This study is the first to report the potential role of NIE in the treatment of liver cancer.